IMF Staff Papers, Volume 53, No. 2. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2006)
Noteworthy among the six papers appearing in this latest issue of the IMF's peer-reviewed journal is another installment in the Special Data Section. Anthony Pellechio and John Cady from the IMF's Statistics Department take a close look at differences in IMF data; how and when they could occur; and what the implications of such differences might be for end-users of the IMF's data.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet